LEADERSHIP ROLE AND EMPLOYEE INTENTION TO STAY: NEW EVIDENCE FROM HEALTHCARE SECTOR IN EMERGING ECONOMIES - Setyaningrum, Retno Purwani; Said, Jamaliah; Soelistya, Djoko (Universitas Brawijaya, Indonesia, 2023)
The report shows that healthcare employees experience more stress, emotional exhaustion, and burnout prevail during and post covid 19 and force employees to leave the profession. However, there are many more who take the challenge by staying on. This research investigates whether servant leadership, work-life balance, and behavior engagement play roles in employee intention to stay. This study surveyed 200 employees of 10 big healthcare companies in Indonesia. The number of respondents who filled out the questionnaire via google form was 137. Data were analyzed using Smart Partial Least Square (PLS). The findings of the study showed that servant leadership has a positive effect on work-life balance, servant leadership has a positive effect on a leader's needs to trust, work-life balance has a positive effect on behavior engagement, work-life balance has a positive effect on leader needs to trust his subordinates, behavioral engagement has a positive effect on the intention to stay, empowerment leader moderates the positive effect of behavior engagement on intention to stay, and leader needs to trust his subordinates has a positive effect on the intention to stay. However, service leadership has no effect on the intention to stay, behavioral engagement has no effect on the leader's need to trust his subordinates, and behavioral engagement has no effect on the leader's need to trust his subordinates. The implication of this research is to retain employees in the company. Although the leadership style is not very supportive, it is still necessary to ensure that the employees feel comfortable at work, trusted by their superiors, and empowered by their abilities.